Family‐based interventions for preventing overweight or obesity among preschoolers from racial/ethnic minority groups: A scoping review - Xiran Wang; Alice Ammerman; Colin J. Orr (Wiley, 2022)
Abstract Objective This scoping review aimed to synthesize the published literature on family‐based childhood obesity prevention interventions from 2015 to 2021 that focused on children 2-5 years of age from racial and/or ethnic minority households. Methods A PICOS (population, intervention, comparison, outcome, and setting) framework was used to guide the development of the research question, search strategy, and inclusion/exclusion criteria. To be included, the study must have been a randomized controlled trial or quasi‐experimental trial that enrolled participants 2-5 years of age and their caregivers who identified as being from a racial and/or ethnic minority group in the United States. The study must have also examined a family‐based intervention that incorporated components to prevent childhood obesity (i.e., fruits and vegetable intake, parental responsive feeding, physical activity), be conducted in a remote (i.e., online, text, mail), home, community, primary care setting, or early childhood education institution setting, and report on body mass index (BMI, kg/m2), BMI z‐score, anthropometric measures (weight, waist circumference, fat mass, etc.), changes in health behaviors, or increase in nutritional knowledge. Results Fourteen individual studies were identified. Most interventions used multiple components for promoting nutritional knowledge and behavioral changes among families. Eight interventions included culturally tailored components targeting four aspects: (1) language barriers, (2) food choices, (3) relationships between family members, and (4) rapport building. Conclusions There is limited research in this field focusing on children from racial and/or ethnic minority groups. Future efforts should invest in developing culturally appropriate interventions for these groups.